YAP and TAZ are distinct effectors of corneal myofibroblast transformation. (March 2019) - Muppala, Santoshi; Raghunathan, Vijay Krishna; Jalilian, Iman; Thomasy, Sara; Murphy, Christopher J.
Abstract: Purpose: Transforming growth factor β1 (TGFβ1) is elevated in wounds after injury and promotes the transdifferentiation of quiescent cells in the stroma (keratocytes, to activated fibroblasts and subsequently myofibroblasts-KFM transformation). Coactivators of transcription, YAP (Yes-associated protein) and TAZ (Transcriptional coactivator with PDZ-binding motif), are mechanotransducers that intersect with the TGFβ pathway via interactions with Smad proteins. Here, we examined the distinct role of YAP and TAZ on TGFβ1 induced myofibroblast transformation of primary human corneal fibroblasts (HCFs). Methods: A knockdown approach was used to silence YAP and TAZ individually in HCFs. Forty-eight hours post siRNA transfection, cells were cultured in the presence or absence of 2 ng/ml TGFβ1 for 24h. The cells were subjected to nuclear and cytoplasmic fractionation. The expression of α-smooth muscle actin (αSMA), Smad 2, 3 and 4, CTGF and phospho-Smad2, 3, and 4 were assessed by qPCR and Western blotting. Results: TGFβ1 stimulation resulted in the decreased phosphorylation of YAP in the cytosol, and increased levels of phosphorylated TAZ and Smad2/3/4 in the nucleus. Knockdown of TAZ resulted in elevated YAP expression but not vice versa. Additionally, knockdown of TAZ but not YAP resulted in upregulation of αSMA expression in the presence and absence of TGFβ1. In the presence of TGFβ1 YAP knockdown increased Smad2/3/4 expression and Smad4 phosphorylation, while TAZ knockdown had no effect on Smad2/3/4 expression and phosphorylation. YAP knockdown inhibited CTGF expression while TAZ knockdown resulted in its increased expression. Finally, simultaneous knockdown of YAP and TAZ resulted in cell death. Conclusion: Our findings suggest that YAP and TAZ function as distinct modulators of TGFβ1 induced myofibroblast transformation and have different roles in signalling. Specifically, TAZ limits YAP's ability to mediate KFM transformation via Smad proteins. The data also suggest that while having distinct effects, YAP and TAZ have redundant or combinatorial functions critical to cell survival. These results suggest that a loss of TAZ may help drive corneal haze and fibrosis and that the balance between YAP/TAZ is essential in controlling myofibroblast differentiation. Highlights: TGFβ1 stimulation decreases cytosolic pYAP and nuclear TAZ, and increases nuclear pTAZ and YAP. TAZ knockdown increased YAP mRNA expression but YAP knockdown did not alter TAZ expression, suggesting TAZ limits YAP. Knockdown of TAZ but not YAP upregulates αSMA expression and promotes KFM transformation. Knockdown of YAP stimulates expression of Smad 2/4, while TAZ knockdown does not alter Smad expression. Knockdown of YAP or TAZ inhibits versus induces CTGF expression, respectively. Double knockdown of YAP and TAZ is lethal.